24-Hour ultra-marathon running: A narrative review of performance factors and physiological impacts - Knechtle, B.; Braschler, L.; Weiss, K.; Scheer, V.; Duric, S.; Leite, L. B.; Forte, P.; Nikolaidis, P. T.; Chlíbková, D.; Rosemann, T. (Sports Medicine - Open, 2026)
The 24-hour ultra-marathon is a specific race format with a long tradition and high popularity. To date, no comprehensive review has systematically summarized the scientific literature on 24-hour ultra-marathon running. We performed a comprehensive search in the PubMed and Scopus databases, covering studies published until the end of 2025. The participation of runners and finishers in 24-hours has increased in the past decades. Most participants in 24-hours are age group or master runners older than 35 years. 24-hour ultra-runners typically cover distances exceeding 100 km per event, with an average distance ranging from ~ 150-160 km, while the top performers can achieve over 200 km. Men achieve greater distances than women. The best performance is achieved at 40-50 years. The most important predictive variables in 24-hours are training, nutrition, previous experience, and pacing; anthropometric characteristics seemed of no predictive value. During 24-hours, athletes ingest mainly carbohydrates and experience an energy deficit, but rarely exercise-associated hyponatremia. A 24-hour run leads to decrease in body mass, which can be due to dehydration, a loss of skeletal muscle mass, and/or a loss of fat mass. A 24-hour run has effects on the cardiovascular system (i.e., decrease in blood pressure, changes in cardiac biomarkers, and changes in electrocardiogram and echocardiographic findings), the kidneys (i.e. reversible impairment of kidney function), the digestive system (i.e., gastrointestinal discomfort, reversible increase in liver enzymes), the immune system (i.e., increase in immune markers) and the hematological system (i.e., decrease in red blood cells, increase in white blood cells). All negative effects are resolved within 2-3 days. In summary, 24-hour ultra-marathon runners are master athletes with extensive experience, optimal training preparation, and optimal nutrition to complete a 24-hour run successfully. The adverse effects on the heart, kidneys, immune system, and digestive tract generally resolve within a few days after the event. Future studies need to investigate nutrition after the race to enhance recovery and the impact of training and competing in this specific race format on the locomotor system (i.e. skeleton, muscles, tendons, joints).